Diabetic microvascular complications and associated factors in patients with type 2 diabetes in Southern Ethiopia - Merid, Fasika; Getahun, Firdawek; Esubalew, Habtamu; Gezahegn, Tamirat (Frontiers in Endocrinology, 2024)
Background: Microvascular complications are long-term complications that affect small blood vessels, usually developed in diabetes, and are primary causes of end-stage renal disease, several painful neuropathies, and blindness. Thus, this study aimed to determine diabetic microvascular complications and factors associated with them among patients with type 2 diabetes. Methods: An institution-based cross-sectional study was conducted among 378 type 2 diabetes patients. The presence of at least one diabetic microvascular complications diagnosed by physicians and found on the record was considered to have microvascular complications. The data was collected by reviewing the medical records of T2DM patients who were on follow-up from January 1, 2012, to December 31, 2021. The collected data was entered into EpiData version 3.1 and analyzed by Stata version 14. Bivariate and multivariable logistic regression were used to identify statistically significant risk factors for diabetic microvascular complications at p-value < 0.05. Results: Patients with type 2 diabetes mellitus had a prevalence of diabetic microvascular complications of 26.5% (95% CI: 22.0%, 30.9%). Diabetic neuropathy was the highest (13.2%), followed by diabetic nephropathy (12.4%), and diabetic retinopathy (6.4%). Increasing age, poor glycemic control, hypertension comorbidity, anemia, positive proteinuria, a longer duration of type 2 diabetes mellitus, and hypercholesterolemia were significantly associated factors with diabetic microvascular complications. Conclusion: Diabetic microvascular complications were highly prevalent. Therefore, the study suggests that interventional strategies should be taken for poor glycemic control, hypertension comorbidity, anemia, positive proteinuria, and hypercholesterolemia to control the development of diabetic microvascular complications in patients with type 2 diabetes.